Poly(amidoamine) dendrimers grafted on electrospun poly(acrylic acid)/poly(vinyl alcohol) membranes for host–guest encapsulation of antioxidant thymol. Issue 33 (3rd August 2017) - Amariei, Georgiana; Boltes, Karina; Letón, Pedro; Iriepa, Isabel; Moraleda, Ignacio; Rosal, Roberto
Abstract : Amino-terminated PAMAM dendrimers were grafted onto poly(acrylic acid)/poly(vinyl alcohol) electrospun fibres to create a host–guest architecture for the controlled delivery of the antioxidant thymol. Abstract : Amino-terminated fifth generation poly(amidoamine) (PAMAM G5-NH2 ) dendrimers were grafted onto the surface of poly(acrylic acid)/poly(vinyl alcohol) (PAA/PVA) electrospun fibres with the purpose of creating a host–guest architecture for the controlled delivery of a natural antioxidant, thymol. The nanofibers were stabilized by esterification crosslinking to produce a water insoluble non-woven membrane. The functionalization with PAMAM G5-NH2 led to dendrimer loadings in the 7.4 × 10 −7 –2.25 × 10 −6 mol dendrimer per g membrane range. The resulting materials were characterized using SEM, ATR-FTIR and surface ζ -potential measurements. The loading capacity for thymol reached 2.5 × 10 −4 mol thymol per g membrane. The membranes were tested for thymol release in different aqueous and non-aqueous food simulants. Computational modelling was used to get a further insight into the host–guest association of thymol and PAMAM G5-NH2 molecules through docking studies. For this purpose, we examined the molecular level details of the dendrimer–guest complex, calculated the number of included or attached molecules, the exact location of thymol in host–guest complexes and the local environment around the thymol molecules. Docking studies showed that PAMAM-G5-NH2 dendrimers can encapsulate thymol molecules through hydrophobic interactions and hydrogen bonding. The maximum amount of thymol molecules theoretically encapsulated was 16, while another 25 could be hosted at the dendrimer surface through interaction with the outer part or the dendritic branches. The experimental value was 37 ± 5, in agreement with theoretical predictions.